Clinical value of 18FDG PET/CT in screening for distant metastases in head and neck squamous cell carcinoma. (20th February 2018) - Deurvorst, S.E.; Hoekstra, O.S.; Castelijns, J.A.; Witte, B.I.; Leemans, C.R.; de Bree, R.
Abstract : Objectives: The detection of distant metastases is of major importance in management of head and neck squamous cell carcinoma patients. Design: All patients underwent 18 FDG PET/CT for the detection of distant metastases. Setting: Retrospective single‐centre study. Participants: Head and neck squamous cell carcinoma patients with high‐risk factors for distant metastases. Main outcome measures: Accuracy of 18 FDG PET/CT for the detection of distant metastases using clinical development of distant metastases and a minimal follow‐up of twelve months as reference standard. Comparison of overall survival between patients diagnosed with distant metastases during initial screening and patients diagnosed with distant metastases during follow‐up. Results: In 23 (12%) of the 190 patients, 18 FDG PET/CT detected distant metastases at screening. Sensitivity and negative predictive value were 46.2% (95% CI 32.6‐59.7) and 82.6% (95% CI 76.8‐88.5). No difference in median overall survival from the time of distant metastases detection was found between patients diagnosed with DM during work‐up or during follow‐up. Conclusions: In head and neck squamous cell carcinoma patients with high‐risk factors, 18 FDG PET/CT has a high negative predictive value for the detection of distant metastases and should be used in daily clinical practice, although the sensitivity is limited when long‐term follow‐up is used as reference standard.